Immunopotentiation properties of propiobacterium granulosum versus vitamin E in cylophoshamide immunosuppressed chickens - Afify, Manal A.; Elshazly, O. A.; Zouelfakar, Sahar A.; Shaheed, Iman B.; Awaad, M. H. H. (2003)
The immunosupressing effect of cyclophosphamide (CP) on cell mediated and humoral immunity has been proven with severe dramatic effect on serum transferrin (Tf) and immunoglobulins (IgG and IgM). Marked alterations in the morphologic features of major lymphoid organs and their weight / body weight indices were evident. The immunoassay revealed that Propiobacterium granulosum immunopotentiated the production of anti-sheep red blood cells (SRBCs) haemagglutinating (HA) antibodies 7 days post immunization till the end of the experiment (42 days) with a geometric mean ranging between 1.8-5.1. While vitamin E humbly sustained the HA titer at 14 and 21 days post immunization with a geometric mean of only 0.5 for each.
Includes references.
Summary in Arabic.
1
Keywords: Chickens -- Immunology; Cyclophosphamide; Immunosupression; Immunoglobulins -- Therapeutic use; Vitamin E -- Therapeutic use